How the Veterinary Feed Directive Affects Cattle Owners - Matt Hersom; Todd Thrift; Joel Yelich (EDIS, 2016)
The Veterinary Feed Directive (VRD) is a federal regulation from the Food and Drug Administration that will change the additives that can be included in animal feed, the ways in which cattle producers manage their animals and veterinarians interact with cattle owners, and the products available for use on the ranch. This 3-page fact sheet provides an overview of the new regulation’s nature, functions, requirements, and implications for cattle owners. Written by Matt Hersom, Todd Thrift, and Joel Yelich, and published by the UF Department of Animal Sciences, July 2016.